Research of operating mode of rhombic gravitational pneumatic classifier - Yukhymenko, Mykola; Ostroha, Ruslan; Litvinenko, Andriy; Piddubnyi, Yevhen; Zabitsky, Dmitry (Technology audit and production reserves, 2018)
The paper discusses the technology of obtaining organic and organo-mineral granules of prolonged action. It is found that the granular marketable product must meet certain requirements for particle size. Consequently, the separation unit (classification) in the developed technological scheme plays a very important role in the process of obtaining commodity pellets. The object of research is the process of classification of granular organic fertilizers in the rhombic gravitational pneumatic classifier. The study is aimed at establishing the optimal mode-technological parameters of the «rhombic» pneumatic classifier. For this, a physical model of the process of pneumatic classification of dispersed particles (granules) in a rhombic form is studied, which explains the conditions for the separation of a polydisperse mixture into narrower fractions, the formation of a suspended layer of material. As well as a cyclic mechanism for loading and unloading the suspended layer. In addition to ensuring the purity of the product, the apparatus should also have a low hydraulic resistance and low power consumption. For physical modeling, a laboratory bench of a rhombic gravitational pneumatic classifier is used, on which a number of experiments are performed on the selection of the optimal separation mode and product purity. Rational use of the working space and effective ways to influence the flow of material within the same building allows to obtain the required separation parameters. Carrying out the classification process in the «rhombic» pneumatic classifier can effectively remove up to 99 % of particles less than 2 mm in size from the granulated product. At the exit of the apparatus, let’s obtain a marketable product with a particle size of 2–4 mm in an amount of 99 %, which corresponds to the standard requirements for a qualitative particle size distribution. Such an effective separation in this apparatus is due to its shape (optimal opening angles and closure of the «rhomb» of the case), which contributes to the rotation of the material flow and leads to an additional reseeding. The absence of contact elements inside the device significantly reduces its hydraulic resistance and reduces energy consumption.